RASIO KEUANGAN DAN FAKTOR LAINNYA YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN NON KEUANGAN - Veronica Veronica; Suryanto Suryanto (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This study aims to examine the factors that affect the value of companies in non-financial companies in Indonesia. There are seven independent variables in this study, including: managerial ownership, firm size, profitability, institutional ownership, capital structure, corporate growth, and liquidity. Eighty-eight companies registered during the period 2014-2016 in Indonesia were selected as samples using purposive sampling method. And data analysis is done by using multiple linear regression method. The results of this study indicate that there is a positive effect of profitability on the value of the company. The capital structure also has a positive effect on firm value, while managerial ownership, institutional ownership, firm size, company growth, and liquidity have no effect on firm value.